1983
DOI: 10.1152/ajpheart.1983.244.3.h328
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazine protection in calcium overload-induced heart failure: a possible role for calmodulin

Abstract: The effect of several phenothiazines on the extent of cellular damage resulting from the calcium paradox was examined. Hearts treated with trifluoperazine, a potent calmodulin inhibitor, exhibited less cellular damage than untreated myocardium as reflected by light microscopy, high-energy phosphate content and the loss of protein and creatine phosphokinase into the perfusate. A dose response of this effect revealed a maximal response at about 1 microM trifluoperazine, a concentration which lies well within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Thus, a new class of agents -calmodulin antagonists -have become useful in assessing the role of calcium in intracellular processes (4,16,32,42). Recently, trifluoperazine (TFP), one of these antagonists (41), was reported to reduce myocardial damage associated with the Ca-paradox (32,33). It raised the possibility that a calmodulin dependent process may be involved in the development of cellular damage of the myocardium (32,33).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a new class of agents -calmodulin antagonists -have become useful in assessing the role of calcium in intracellular processes (4,16,32,42). Recently, trifluoperazine (TFP), one of these antagonists (41), was reported to reduce myocardial damage associated with the Ca-paradox (32,33). It raised the possibility that a calmodulin dependent process may be involved in the development of cellular damage of the myocardium (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, trifluoperazine (TFP), one of these antagonists (41), was reported to reduce myocardial damage associated with the Ca-paradox (32,33). It raised the possibility that a calmodulin dependent process may be involved in the development of cellular damage of the myocardium (32,33). *) This study was supported by the grant W.10.8.4.13.05 347 To verify this hypothesis further we have examined the effects of TFP and compound R 24571 on hearts subjected to hypoxia and reoxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of that, TFP has been found to protect myocardial cells against damage resulting from the Ca 2+ paradox [24]. Previous studies [10] as well as our own [12] have shown the cardioprotective effects of TFP against myocardial ischemic and reperfusion injury when applied in the face of an ischemic insult.…”
Section: Discussionmentioning
confidence: 87%
“…It is also likely that most of the stabilizing potency of TFP rises from its antiphospholipase activity (1,37). The phenothiazines have been previously shown to protect the heart against disturbances in phospholipid metabolism as well as against reperfusion calcium-mediated damage (35).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the presence of calmodulin in the myocardium, its certain activation during calcium overload (35) and the ability to alter many aspects of intracellular metabolism involving stimulation of membrane-associated PLA2 the above proposal seems rather reasonable.…”
Section: Discussionmentioning
confidence: 99%